2010
DOI: 10.1111/j.1469-8749.2010.03772.x
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental assessment of children with major non‐cardiac congenital anomalies predicts development at the age of 5 years

Abstract: MDI Mental Developmental Index PDIPsychomotor Developmental Index SES Socioeconomic status TIS Total impairment score AIM The aim of this study was to evaluate cognitive and motor development in children with major congenital anomalies and the predictability of development at age 5 years.METHOD A prospective, longitudinal follow-up study was undertaken. The Dutch version of the Bayley Scales of Infant Development -Mental Developmental Index (MDI) and Psychomotor Developmental Index (PDI) -were administered at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 15 publications
6
51
3
Order By: Relevance
“…The incidence of severe developmental delay in both groups (3 and 3%) seems in line with the incidence of severe delay in the general population (2.3%) [8]. None of the children had cerebral palsy, bilateral blindness or deafness.…”
Section: Discussionsupporting
confidence: 59%
“…The incidence of severe developmental delay in both groups (3 and 3%) seems in line with the incidence of severe delay in the general population (2.3%) [8]. None of the children had cerebral palsy, bilateral blindness or deafness.…”
Section: Discussionsupporting
confidence: 59%
“…20 -22 Parents' ethnicity was used because a child's verbal skills and thus neurodevelopmental outcome may be affected by a parent who was born outside of the Netherlands and does not have Dutch as their first language. 21 The influence of medical characteristics on IQ and selective attention at 8 years of age was tested in 2 separate models. Diagnosis, type of ECMO, duration of mechanical ventilation, and chronic lung disease were added into the multivariate linear regression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is in line with previous cross-sectional studies. 2,3,7,8,21 Strikingly, a large group of children attending regular education needed extra help in school, despite average intelligence. We found that these school difficulties were related to selective attention problems.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate has decreased from 33 to 12% since this protocol was implemented [2]. Consequently, worldwide the focus of interest has shifted to morbidity [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%